Mouse Model of Critical Persistent Inflammation, Immunosuppression, and Catabolism Syndrome. Issue 2 (20th October 2021) - Chen, Xiancheng; Li, Xiaojing; Lu, Huimin; Xu, Yali; Wei, Yu; Cao, Ke; Zhu, Zhanghua; Chen, Ming; Yu, Wenkui
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Persistent inflammation, immunosuppression, and catabolism syndrome (PIICS) is a growing challenge in intensive care units (ICUs). PIICS causes a severe illness with high mortality. Currently, treatment is expensive, and the outcomes are dismal. Herein, we established a PIICS model to study the disease pathophysiology and its potential treatment. Using a modified sublethal cecal ligation and puncture (CLP) to induce sepsis (day 1) and the injection of lipopolysaccharide (LPS) to induce an aggravated inflammation response (day 11), CLP + LPS mice recapitulating PIICS features were successfully generated (day 14). Adult male mice were divided into CLP + LPS, CLP + daily chronic stress (DCS), CLP, DCS, LPS, and sham control groups. A survival curve was generated, and phenotypes were analyzed using markers for catabolism, inflammation, and immunosuppression. The CLP + LPS model showed two mortality peaks (after CLP and after LPS), whereas the CLP + DCS and CLP groups showed one peak. Surviving CLP + LPS mice exhibited significantly increased catabolism and inflammatory cytokine levels and aggravated inflammation, including organ inflammation. CLP + LPS mice exhibited strong immune suppression as evidenced by decreased splenic cluster of differentiation (CD)8 + and interferon-γ + CD8 + T cell counts and a concomitant and significant increase in the myeloid-derived suppressor cell population. This CLP+LPS-induced PIICS model differs from acute sepsis models, showing two mortality peaks and a protracted course of 14 days. Compared to previous PIICS models, ours shows a re-aggravated status and higher catabolism, inflammation, and immunosuppression levels. Our aim was to use the PIICS model to simulate PIICS pathophysiology and course in the ICU, enabling investigation of its mechanism and treatment.